Epstein-Barr Virus (EBV)-positive Sporadic Burkitt Lymphoma: An Age-related Lymphoproliferative Disorder?. (February 2015) - Satou, Akira; Asano, Naoko; Nakazawa, Atsuko; Osumi, Tomoo; Tsurusawa, Masahito; Ishiguro, Atsushi; Elsayed, Ahmed Ali; Nakamura, Naoya; Ohshima, Koichi; Kinoshita, Tomohiro; Nakamura, Shigeo
Abstract : Epstein-Barr virus (EBV) is detected in 20% to 30% of sporadic Burkitt lymphoma (sBL). However, only a few studies of EBV-positive (EBV + ) sBL have been reported, and its characteristics still remain controversial. To highlight the features of EBV + sBL, we compared the clinicopathologic characteristics of 33 cases of EBV + and 117 cases of EBV-negative (EBV − ) sBL in Japan. EBV + sBL showed significantly higher age distribution (median, 42 vs. 13 y; P <0.0001) and higher frequency of patients older than 50 years (48% vs. 16%, P <0.0001). We also revealed the difference of the involved sites. The EBV + group showed significantly higher incidence of involvement of tonsil ( P =0.027), adrenal gland ( P =0.011), and cervical lymph node ( P =0.040). In addition, the EBV + group tended to have higher incidence of nodal involvement ( P =0.078) and involvement of para-aorta lymph node ( P =0.084) and heart ( P =0.050). In contrast, the gastrointestinal tract was less frequently affected in EBV + sBL ( P =0.024). In addition, the less positivity for MUM1 ( P =0.020) of EBV + sBL was highlighted. These results indicate that biological behavior and pathogenesis of EBV + sBL might be different from those of EBV − sBL. Our results demonstrate that EBV + sBL has an aspect of age-related disease and is a distinct clinicopathologic subtype, which should be distinguished from EBV − sBL.